Eco-Waste Stove: Teknologi Konversi Limbah Kayu Menjadi Energi Ramah Lingkungan Berbasis Circular Economy di Desa Tadukan Raga, Kecamatan STM Hilir, Deli Serdang: Indonesia - Sidabutar, Rivaldi; Revadi, Chindy Elsanna; Harahap, Muthiah Putrilan Syamnah; Buysang, Luke Gilbert; Silaban, Selvia Geraldine; Silalahi, Nova Ronauli; Ramadani, Khori; Hasibuan, Fairuz Fuad; Butarbutar, Maya Azhari (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Tadukan Raga Village in Deli Serdang Regency has significant potential in utilizing agricultural wood waste as a renewable energy source. This community service program aims to develop appropriate technology in the form of a briquette press unit and an Eco-Waste Stove biomass cooker. The implementation methods included field surveys, Focus Group Discussions (FGDs), socialization, training, and community mentoring. Wood waste was processed through pre-treatment, mixing with adhesive, pressing, and drying to produce high-quality briquettes. These briquettes were then used as fuel for the Eco-Waste Stove, which was designed to be more efficient, environmentally friendly, and cost-effective compared to traditional combustion. The results showed improved community knowledge, skills, and participation in transforming wood waste into alternative energy. This program not only reduces agricultural waste but also supports circular economy practices, enhances local income, and strengthens rural energy resilience. With continuous support, this technology has strong potential to be replicated in other regions.